2016
DOI: 10.1111/his.12943
|View full text |Cite
|
Sign up to set email alerts
|

Histological spectrum of angiofibroma of soft tissue: histological and genetic analysis of 13 cases

Abstract: Aims: Angiofibroma of soft tissue (AFST) is a rare soft tissue neoplasm characterized by a fibroblastic cytomorphology and a prominent vascular structure. AFSTs possess a novel fusion gene, i.e. NCOA2-AHRR/ AHRR-NCOA2 or GTF2I-NCOA2, providing a useful approach to diagnosing AFST. Morphologically, AFSTs span a wide spectrum, making diagnosis a challenge. The aim of this study was to review AFST cases and to report previously unknown histological features, which we confirmed by genetic analysis. Methods and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
55
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 11 publications
(18 reference statements)
16
55
1
2
Order By: Relevance
“…In accordance with the series investigated by Jin et al and Yamada et al, our data suggest that AHRR‐NCOA2 is the most common fusion gene in STAF with in‐frame fusion transcripts of exon 10–14 ( n = 4), exon 10–16 ( n = 2), exon 9–16 ( n = 2), exon 9–14 ( n = 1), and exon 8–11 ( n = 2). The exon combination 8 ‐ 11 was found by RNA sequencing and has not been reported previously.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with the series investigated by Jin et al and Yamada et al, our data suggest that AHRR‐NCOA2 is the most common fusion gene in STAF with in‐frame fusion transcripts of exon 10–14 ( n = 4), exon 10–16 ( n = 2), exon 9–16 ( n = 2), exon 9–14 ( n = 1), and exon 8–11 ( n = 2). The exon combination 8 ‐ 11 was found by RNA sequencing and has not been reported previously.…”
Section: Discussionsupporting
confidence: 92%
“…Recurrent fusion genes, recognized as driver mutations, are being discovered in a growing number of tumor types, resulting in a specific transcription program of different target genes, which in turn has clinicopathological implications . One example of such a tumor type is the recently delineated benign mesenchymal lesion STAF, which has, in addition to a distinct fibrovascular histological appearance, a AHRR‐ NCOA2 fusion transcript in a large subset of cases …”
Section: Discussionmentioning
confidence: 99%
“…Occasional cases may exhibit scattered cells that stain for CD34, SMA and desmin (2). Previous immunohistochemical studies have revealed that CD163 and ER are useful markers in the diagnosis of AFST (3,4), as in the present case. S-100 protein expression is consistently negative (1).…”
Section: Discussionsupporting
confidence: 63%
“…In addition, Arbajian et al (6) demonstrated a general transcription factor IIi (GTF2I)-NCOA2 fusion gene in a AFST with a three-way t(7;8;14)(q11;q13;q31) translocation, emphasizing the role of NCOA2. Furthermore, a small proportion of NCOA2 gene rearrangement-positive cells have been observed in almost all cases by fluorescence in situ hybridization (3,7). However, it has been noted that a substantial subset of AFSTs were negative for the fusion gene (3,5), as in the current case.…”
Section: Discussionsupporting
confidence: 60%
“…First, a novel GTF2I/NCOA2 fusion gene was identified in Soft Tissue Angiofibroma (fibrovascular tumor of unknown cellular origin) (50,51). A fusion product of t(7;8;14)(q11;q13;q31) resulted in two transcripts: one with an in-frame fusion of part of exon 14 of GTF2I with part of exon 15 of NCOA2 whereas the other one consisted of an out of-frame fusion of part of exon 11 of GTF2I with part of exon 14 of NCOA2 (51).…”
Section: Tfii-i In Cancermentioning
confidence: 99%